Using Mentimeter to Elicit Student Responses in the EAP/ESP Classroom. (April 2020) - Moorhouse, Benjamin Luke; Kohnke, Lucas
The affordances and pedagogical benefits of technology in the English for Specific Purposes (ESP) and English for Academic Purposes (EAP) classrooms are widely acknowledged. One potential use of technology is in eliciting and managing students' responses, which is an area where EAP/ESP teachers often report difficulties. Traditionally, teachers either nominate students to respond or rely on students volunteering to answer questions. In practice, this condition tends to mean that the more confident students respond, or students are 'put on the spot' by being nominated to speak by a teacher. One way to address this issue is through response cards. Students can respond in unison with a card or whiteboard displaying the answer. Response cards are effective at all levels of education. They increase active responses, improve test scores, and motivate learners. There are now digital alternatives to response cards called 'student response systems' (SRS). These systems provide a flexible and diverse way for students to respond using their mobile devices. SRS include Mentimeter, Kahoot, Plickers, GoSoapBox, and Poll Everywhere. Due to its versatility and unlimited number of participants, we believe Mentimeter has greater potential in the EAP/ESP classroom. This tech review will provide an overview of Mentimeter's features and potential uses.